Modeling Electrothermal Feedback of Superconducting Nanowire Single-Photon Detectors in SPICE - Nguyen, Hanson; Simon, Alejandro; Foster, Reed; Berggren, Karl K. (IEEE transactions on applied superconductivity, 2025)
Superconducting nanowire single-photon detectors (SNSPDs) exhibit complex switching behaviors due to electrothermal feedback during the detection process. Modeling and understanding these behaviors are integral for designing superconducting devices; however, many models often prioritize accuracy over computational speed and intuitive integration for circuit designers. Here, we build upon a growing architecture of simulation program with integrated circuit emphasis tools for superconducting nanowire devices by capturing complex residual heating effects in a compact thermal model of an SNSPD. We demonstrate that our model is comparable to more complicated thermal models of superconducting nanowire devices, including finite-element simulations, and is applicable for the fast development of SNSPD circuits.